Church School Students’ Narratives on Their Schools and the Hidden Curricular Effects - Kodácsy-Simon, Eszter (Journal of empirical theology, 2023)
The particular atmosphere of church schools in Hungary is an exciting field of research. Of special interest is the question as to how students perceive their schools, what image they construct of them, and what they think about its purposes and hidden messages. In our exploratory research, we conducted 37 student interviews, followed by content analysis, during which we identified “diversity” as a core concept with multiple associations. Diversity was frequently mentioned in relation to different aspects of school life, but was also discussed as an important reference point in connection with their experience of faith. Diversity is also a personal resource for students when they reflect on specifically relevant and sensitive issues in their lives. This paper presents a conceptual web of diversity identified as a core concept in the students’ narratives.